Legal Adaptation for Muslim Minorities: A Reconstruction of Fiqh al-Aqalliyyat through the Methodological Frameworks of Abdullah bin Bayyah and Muhammad Yusri Ibrahim - Nur Solikin; Syaiful Ahyar; Muhamad Zaenal Muttaqin; Mochamad Syaefudin; Hilmi Ridho (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
This article examines the reconstruction of fiqh al-aqalliyyat as a framework for legal adaptation addressing the complex socio-legal challenges faced by Muslim minorities in non-Muslim majority societies. It focuses on the methodological frameworks developed by Abdullah bin Bayyah and Muhammad Yusri Ibrahim, two prominent contemporary scholars whose works have significantly shaped minority jurisprudence. Employing a comparative doctrinal and analytical approach, this study examines their primary writings sinaʿat al-Fatwa wa Fiqh al-Aqalliyyat and Fiqh al-Nawazil li al-Aqalliyyat al-Muslimah to identify the epistemological foundations, legal reasoning patterns, and normative objectives underlying their approaches. The findings demonstrate a clear methodological divergence: Ibn Bayyah emphasizes maqāṣid al-shariʿah, tahqiq al-manat, and contextual legal reasoning rooted in the Maliki tradition to enable adaptive and purpose-oriented rulings, while Yusri Ibrahim adopts a more textualist and precedent-based framework within the Hanbali school, prioritizing juristic continuity and doctrinal restraint. This article argues that fiqh al-aqalliyyat should be understood not merely as a collection of legal concessions (rukhaṣ), but as a systematic methodological paradigm that negotiates normative fidelity and contextual responsiveness. By reframing minority fiqh through the lens of legal adaptation, this study contributes to contemporary debates on Islamic legal methodology, minority rights, and the future development of Islamic jurisprudence in pluralistic societies.